Preoperative antidepressant use in patients with depression is associated with increased complications and additional shoulder procedures following rotator cuff repair - Brady P. Moore, BS; Sterling J. DeShazo, BS; Jeremy S. Somerson, MD (JSES International)
Background: Preoperative depression has been associated with inferior functional outcomes and increased complications following arthroscopic rotator cuff repair (RCR). This study evaluated the association of antidepressant use with postoperative complications following arthroscopic RCR. Methods: The TriNetX database was used to evaluate postoperative outcomes of patients who underwent arthroscopic RCR from February 24, 2004 to February 24, 2024. Patients diagnosed preoperatively with depression and documented antidepressant use within 1 year preceding surgery were compared to patients with preoperative depression but no history of preoperative antidepressant use. The cohorts were propensity-matched for demographic factors including age, type 2 diabetes, nicotine dependence, alcohol-related and opioid-related disorders, and indicators of depression severity (eg, suicide attempt, history of self-harm, sleep disorders). Outcomes were evaluated within 90 days and 3 years postoperative. Results: A total of 9151 patients with documented antidepressant medication use were matched with 5894 patients with no antidepressant use. Patients using antidepressants demonstrated significantly higher odds of acute postoperative pain (P < .0001), shoulder stiffness (P = .0011), and emergency department visit (P < .0001) within 90 days postoperative and significantly increased odds of shoulder pain (P < .0001); RCR revision surgery (P < .0001); shoulder arthrocentesis, aspiration, and/or injection (P < .0001); and shoulder arthroplasty (P < .0001) within 3 years postoperative. Conclusion: Preoperative antidepressant use was associated with significantly increased odds of acute postoperative pain, emergency department visits, opioid abuse, and additional shoulder procedures following arthroscopic RCR and did not mitigate the deleterious impact of depression on arthroscopic RCR outcomes.